2010
DOI: 10.1016/j.jchas.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dust explosion causation, prevention and mitigation: An overview

Abstract: The current paper gives a general overview of factors that can cause a dust explosion and the means by which such an event can be prevented and mitigated. Important explosibility parameters (e.g., maximum explosion pressure and standardized maximum rate of pressure rise) are described in terms of their relation to explosion causation, prevention and mitigation. Causation is further explained by means of the fire triangle and the explosion pentagon, and standard risk reduction measures are placed in a hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 207 publications
(84 citation statements)
references
References 10 publications
0
82
0
2
Order By: Relevance
“…The amount of fuel available for an explosion can be eliminated or significantly reduced by performing proper housekeeping practices. 1,10 Substitution involves replacing a hazardous material or work procedure with one that is safer. Two examples are: to use an explosion proof vacuum cleaner instead of sweeping dust, or to substitute a combustible dust with a non-explosible powder.…”
Section: Inherent Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of fuel available for an explosion can be eliminated or significantly reduced by performing proper housekeeping practices. 1,10 Substitution involves replacing a hazardous material or work procedure with one that is safer. Two examples are: to use an explosion proof vacuum cleaner instead of sweeping dust, or to substitute a combustible dust with a non-explosible powder.…”
Section: Inherent Safetymentioning
confidence: 99%
“…Two examples are: to use an explosion proof vacuum cleaner instead of sweeping dust, or to substitute a combustible dust with a non-explosible powder. 1,10 Moderation involves reducing the potential severity of an explosion. This includes increasing the particle size of a powder to reduce potential ignition, changing the composition of the dust by admixing inert dust, or controlling the effects of a process upset by spacing out equipment.…”
Section: Inherent Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…40 standard sieve (Amyotte & Eckhoff, 2010). A dust explosion can be defined as the rapid combustion of flammable particulates suspended in air (Abbasi & Abbasi, 2007).…”
Section: Dust and Hybrid Mixture Explosionsmentioning
confidence: 99%
“…Nevertheless, they may, in combination, create an explosible mixture (Amyotte & Eckhoff, 2010). Eckhoff (2003) demonstrated that the addition of flammable gas to a dust cloud significantly increases the explosion violence.…”
Section: Dust and Hybrid Mixture Explosionsmentioning
confidence: 99%